Research progress on the therapeutic effect and mechanism of Akkermansia Muciniphila on metabolic diseases - CUI Xin; ZHANG Yangyang; CHEN Lina (Guangxi Yike Daxue xuebao)
Metabolic diseases are a kind of chronic diseases caused by abnormal metabolism of matter or energy, including obesity, diabetes and non-alcoholic fatty liver disease, etc., which have seriously harmed people's health. Studies have shown that the imbalance of gut microbiota is closely related to the occurrence and development of various metabolic diseases, and the regulation of gut microbiota may have positive significance in improving metabolic diseases. Akkermansia muciniphila is a new type of probiotic, which may have protective effects on metabolic diseases by repairing intestinal barrier, regulating gut microbiota and improving host metabolism. In order to provide theoretical basis for clinical treatment, this paper reviews the research progress on the therapeutic effect and mechanism of Akkermansia muciniphila on metabolic diseases, including obesity, diabetes and nonalcoholic fatty liver disease.